SKILLS AND PERSONAL ABILITIES NEEDED FOR THE DEVELOPMENT OF FUTURE TEACHERS: A CASE STUDY IN SUPERVISED INTERNSHIPS AT UFABC - Silva, Alexandre Leite da (2025)
The purpose of the supervised internship is to provide graduates with an approximation of the reality in which they will work after graduating and entering their field of work. During the pandemic period, when universities had to make decisions about how to continue teaching and learning during social isolation, interns learned that it was essential for future teachers to develop skills in using educational technologies to teach remotely, since this modality must be part of a permanent scenario.  The objective of this article is to report a case study developed with a group of students in the Supervised Internship in Chemistry discipline at a federal public university in the state of São Paulo, investigating, in addition to technological skills, which other skills the students perceived as important for be developed increasingly considering distance learning modalities as possibilities where the future professional teacher can work. This is qualitative research, approached as a case study, whose data collection was carried out through individual questionnaires with open questions. The analysis of the results obtained shows that technological skills and personal skills/qualities (Le Boterf), mobilized in internship experiences in the remote context, go hand in hand in the teaching and learning process and should be part of the training of future teachers considering the new reality. We consider the field of supervised internships as privileged for this purpose, given its dynamic nature, which is more appropriate to contexts in constant change.